Global Transition Online - Ragoussis, Alexandros (Washington, DC: World Bank, 2022)
This paper presents new evidence on the growth of digital technology in response to the COVID-19 pandemic. It uses the largest and most comprehensive database available to analyze website birth dynamics and the uptake of website technologies. The database comprises 150 million active websites and 27,000 technologies. The findings show that, over 2020, there was rapid adoption of both e-commerce and online payments across all countries, with greatest rates of adoption in countries that had lower initial levels of technology use. The timing of COVID-19 lockdowns strongly predicts increased use of these technologies, accounting for about a third of the overall increase in e-commerce or online payments usage over 2020. More importantly the shock appears to have resulted in a shift in trend more so than a shift in level, suggesting that COVID-19 may have transformed the trajectory of online market growth.